A highly augmented, (12,3)-connected Zr-MOF containing hydrated coordination sites for the catalytic transformation of gaseous CO2 to cyclic carbonates - Schmitt, Wolfgang (My University, 2019)
A porous Zr-based MOF, [Zr6(BTEB)4(μ3-O)4(μ3-OH)4(H2O)4], which contains partially hydrated, 12-connected {Zr6} nodes and extended carboxylate ligands (BTEB3−), was synthesized and physicochemically characterised. The resulting (12,3)-connected, 3D framework adopts an uncommon llj topology with a large, solvent accessible void volume of ca. 79% of the unit cell volume. The porous structure facilitates the uptake of N2 and activated samples give rise to BET surface areas of >1000 m2 g−1. Furthermore, the porosity and accessibility of Lewis acidic Zr(IV) sites promote the catalytic transformation of gaseous CO2 to cyclic carbonates via cycloaddition reactions using epoxide reactants, whereby solvated MOFs exhibit higher catalytic performance than thermally treated samples.
PUBLISHED